DUAL FORM OF EDUCATION IN THE CONTEXT OF IMPLEMENTING SUSTAINABLE DEVELOPMENT GOALS (Innovative professional education, 2024)
The article presents an analysis of the experience of dual education in Ukraine at all levels of training of future specialists – vocational, professional pre-university and higher education. The reasons that hindered its implementation, reducing the effectiveness of itsimpact on the sustainable development of society, are described, and prospects for further development are outlined. The influence of dual education on the implementation of the Sustainable Development Goals and meeting the needs of post-war reconstruction ofUkraine is substantiated. It has been found that dual education should not be of a mass nature, but in Ukraine, it is subject to high social expectations to accelerate the post-war recovery of the national economy, meet the growing demand for highly qualifiedpersonnel in strategically important areas of activity (energy, ecology, construction, engineering, agriculture), accelerate European integration and ensure sustainable development of Ukrainian society.
Keywords: dual education; professional, vocational pre-university and higher education; sustainable development of society